Electric pulse improving the plasticity of the HAl66-6-3-2 alloy by promoting the formation of specific oriented texture - Bobo Lu; Kai Tang; Mingxia Wu; Yi Yang; Gang Yang (Materials & Design)
Electric pulse treatment (EPT) effectively enhances material plasticity but typically compromises strength, and the combined mechanisms of pulsed current on dislocation evolution and grain rotation remain unclear. Here, HAl66-6–3-2 alloy was subjected to EPT, and the results revealed that the EPT sample achieved an increase in plasticity without compromising the strength, with an elongation rate enhancement of 69.89 %. The changes in performance are mainly attributed to three aspects: grain refinement, slight decrease in dislocation density, and the formation of strong {632}<223> texture during the EPT. Unlike the untreated (UT) samples with entangled dislocations, under the coupling effect of Joule heating and non-thermal effect, the dislocations in EPT samples exhibited directionality, primarily composed of a series of parallel dislocation pairs. The formation of the strong {632}<223> texture primarily relied on grain boundary migration and grain rotation, with both Joule heating and non-thermal effect facilitating rapid grain boundary migration. At low-angle grain boundaries, the pulsed current facilitated grain rotation, transforming low-angle grain boundaries in the β phase into high-angle grain boundaries. The study demonstrates EPT can promote the movement of atoms and regulate the microstructure, which is of great significance for the subsequent control of alloy properties.